1985
DOI: 10.1042/bj2300785
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of constituent enzyme fractions of mycobacillin synthetase

Abstract: The enzyme fraction A, a constituent enzyme of the three-fraction enzyme mycobacillin synthetase, independently and sequentially activated five amino acids starting from L-proline, producing the pentapeptide Pro(Asp1,Glu1,Tyr1)Asp. The fractions B and C were unable to function independently. However, the fraction B synthesized the nonapeptide Pro(Asp3,Glu1,Tyr2,Ser1)Leu, sequentially activating the pentapeptide and next four amino acids, whereas the fraction C synthesized mycobacillin by the sequential activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…We here report a continuation of our previous work on the functional characterization of constituent enzymes of the three-fraction enzyme mycobacillin synthetase, which showed that fraction A formed the first initiating complex with L-proline in the presence of ATP, that fraction B formed the second initiation complex with pentapeptide in the presence of ATP and that fraction C formed the third or last initiation complex with nonapeptide in the presence of ATP (Ghosh et al, 1985). The present work reports elongation studies demonstrating that fraction A converted tripeptide in the presence of ATP and the next amino acid in the sequence into tetrapeptide and, again, converted tetrapeptide into pentapeptide (also in the presence of ATP and the next amino acid in the sequence), thus lengthening the chain by one amino acid in the presence of ATP for the two successive steps.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We here report a continuation of our previous work on the functional characterization of constituent enzymes of the three-fraction enzyme mycobacillin synthetase, which showed that fraction A formed the first initiating complex with L-proline in the presence of ATP, that fraction B formed the second initiation complex with pentapeptide in the presence of ATP and that fraction C formed the third or last initiation complex with nonapeptide in the presence of ATP (Ghosh et al, 1985). The present work reports elongation studies demonstrating that fraction A converted tripeptide in the presence of ATP and the next amino acid in the sequence into tetrapeptide and, again, converted tetrapeptide into pentapeptide (also in the presence of ATP and the next amino acid in the sequence), thus lengthening the chain by one amino acid in the presence of ATP for the two successive steps.…”
Section: Discussionsupporting
confidence: 59%
“…The synthesis of mycobacillin (Majumder & Bose, 1958), a cyclotridecapeptide antibiotic (L-Pro-D-Asp-D- (Majumder & Bose, 1960), is catalysed by the three-fraction (A, B and C) enzyme complex mycobacillin synthetase (Ghosh et al, 1983), which was purified to homogeneity (Ghosh et al, 1986). The synthesis occurs by three-step process, the enzyme fraction A synthesizing pentapeptide in the first step, fraction B the nonapeptide in the second step, and fraction C completing the molecules in the third step (Ghosh et al, 1985). None of the fractions contains the pantothenic acid arm , but instead a sequential activation of an amino-aciddependent ATP,--[32P]PI exchange reaction (Sengupta & Bose, 1972, 1974 is carried out instead of individual activation, as is the case for other bioactive peptides (Itoh et al, 1968;Gevers et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Finally each of the active fractions was concentrated and separately layered over a discontinuous sucrose gradient (10%, 12.5%, 15%, 17.5 %, 20o%, 22.5 %, w/v) and centrifuged for 8 h at 40000 rev./min in Beckman SW 40 rotor at 0 'C. All the subsequent studies were performed with these active fractions (Ghosh et al, 1985).…”
Section: Purification Of Mycobacillin Synthetasementioning
confidence: 99%